Information Literacy Challenges in Rural: A Qualitative Study on Access and Use of Information Sources in the Village of Bandar Setia - Tamara Nur Hasana; Franindya Purwaningtyas (Universitas Muhammadiyah Enrekang, 2023)
This research aims to determine the challenges of information literacy in the community regarding access and use of information sources in Bandar Setia village. The purpose of this research is to determine the challenges of information literacy regarding asking access and the use of information literacy in the Bandar Setia village community. The research method used in this research is qualitative. The research results show that the challenges of information literacy regarding access and use of information sources are very dynamic, because each society experiences changes in access behavior because it is influenced by technological developments as well as internal and external characteristic factors in each generation. The stages of starting, chaining, exploration, collecting, extracting, verifying and ending may not be passed or carried out by young people and old people if the information they access is not scientific information.